Trends and Rural-Urban Differences in Asthma Hospitalizations in Saskatchewan 1970-1989. Issue 4 (1994) - Senthilselvan, A
Abstract : OBJECTIVE: To examine the trends in hospitalization rates for atsthma in Saskatchewan from 1970 to 1989 and to investigate the differences in asthma hospitalization rates between rural and urban dwellers. DESIGN: Asthma hospitalization rates were calculated for the age groups O to 4, 5 to 9. 10 to 14, 15 to 24. 25 to 34. 35 to 49 and 50 to 64 years for the period between 1970 and 1989. Only the first admission in each year for each person was included in the analysis. As the classification of asthma changed in 1978. trends in asthma hospitalization rates were investigated separately for the periods 1970 to 1978 and 1979 to 1989. respectively. Rate ratios were obtained for male/female and rural/urban comparisons by fitting Poisson regression models. SETTING: The hospitalization data for respiratory diseases for the province of Saskatchewan were examined by age group, sex and place or residence. RESULT: No significant increases were observed in asthma hospitalization rates lrorn 1970 to 1978. In the period 1979 to 1989. asthma hospitalization rates increased significantly among children under four years from 4.31/1000 in 1979 to 7.04/1000 in 1989. Among children under 14 years. asthma hospitalization rates were greater in boys than in girls . The converse was true for adults aged 15 and above, with women having a higher hospitalization rate for asthma than men . In adults aged 35 and above. rural dwellers had higher hospitalization rates for asthma than urban dwellers throughout the study period. In other age groups, although rural dwellers had higher asthma hospitalization rates than did urban dwellers during 1970 to 1984. the differences disappered duri ng 1985 to 1989. CONCLUSION: Further studies are required to find reasons for the increase in asthma hospitalizations among young children under four years old and for the differences between rural and urban dwellers in the age group 35 years and above.